Mass closure models for a system code based on six fields. (January 2017) - Roth, Glenn A.; Aydogan, Fatih
Abstract: System codes are used to analyze nuclear reactor systems during steady state and transient operations. These codes are able to predict pressure drop, void fraction distributions and temperature distributions for various coolants, geometries, and configurations. They also include models for various two-phase flow regimes. However, extreme flow conditions that involve significant phase change can tax the current code capabilities. A set of governing equations for a six-field model have been developed to improve the two-phase modeling capabilities of system codes. The six-field model includes continuous liquid, continuous vapor, large bubble, small bubble, large droplet, and small droplet fields. The governing equations derived previously track the mass, momentum, and energy balances for each of these fields. The mass closure relationships provide necessary components of the governing equations - the source terms for small droplets generated due to large droplet breakup, large bubble generation by coalescence, mass transfer due to phase change, and other physical mechanisms. The six field equations add several new variables to the system of governing equations. The closure models solve for these variables. Therefore, the increased number of governing equations requires several additional closure equations for solution. These closure equations are challenging to define for two-phase flow problem conditions. The necessary closure models to solve the six-field mass balance equations are defined in this work. For the case of some bubble interactions, suitable models have not been identified. For these cases, substitute models are recommended from the droplet closure models. Highlights: We define the needed information to close the six-field mass balance equations. We discuss available models to generate the needed data. We select models to close the mass balance equation.